Radiation transmission of colemanite, tincalconite and ulexite for 6 and 18 MV X-rays by using linear accelerator - Demir, Faruk; Un, Adem (Pergamon-Elsevier Science Ltd, 2013)
Tincalconite, ulexite and colemanite are boron ores. Since these ores include boron, hydrogen and many other elements, these boron ores may be used as shielding materials instead of Pb metal and paraffin wax. In this study, measurements have been made to determine radiation transmission of tincalconite, ulexite and colemanite by transmission method for 6 and 18 MV using linear accelerator (LINAC) with ionization chamber. The experimental results were compared to the results of WinXCom X-ray computer program's. In pair production region, ores such as colemanite, ulexite and tincalconite can be preferred as shielding materials to prevent photon and neutron particle radiations. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Radiation transmission; Attenuation coefficient; Boron; Ulexite; Tincalconite; Colemanite